2010
DOI: 10.1007/s11740-010-0216-7
|View full text |Cite
|
Sign up to set email alerts
|

Static compensation for elastic tool and press deformations during deep drawing

Abstract: Although today's deep drawing tools are thoroughly designed and calculated by means of computeraided design (CAD), finite element (FE) simulation and computer-aided manufacturing (CAM), the sequence of operations to put a tool into production still encompasses manual and irreproducible labor. In particular, the die spotting is empirical and is almost entirely dependent on the toolmaker's experience. This fine-tuning of the drawing tool consumes a large amount of time. In minimizing manual die spotting, a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous research and experience points to many advantages if sheet metal forming is simulated with elastic dies [1][2][3][4][5][6][7][8]. Some areas that are enabled by simulations with elastic dies are virtual spotting, improved digital twins, and improved production support.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research and experience points to many advantages if sheet metal forming is simulated with elastic dies [1][2][3][4][5][6][7][8]. Some areas that are enabled by simulations with elastic dies are virtual spotting, improved digital twins, and improved production support.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason is the lack of die CAD models before the later stages of stamping projects. Previous research during the last couple of decades indicated large benefits if elastic dies and presses are included in SMF simulations [1][2][3][4][5][6][7][8]. The benefits of simulations with elastic tools are also seen in related manufacturing techniques using dies and presses.…”
Section: Introductionmentioning
confidence: 99%
“…This is an approximated method, where the accuracy is defined by the number of deformation modes used ( Struck et al, 2008 ). Großmann et al (2009) proposed an iterative method to adjust the shape of the forming tools to compensate its elastic deformation. The results show a significant influence of the tool deflection in the draw-in, mostly due to the distribution of the blank-holder force, which is higher on the die corners .…”
Section: Introductionmentioning
confidence: 99%